SOCIAL CAPITAL IN EMPOWERING WOMEN FARMER GROUPS IN DUSUN SUMURJURANG KELURAHAN SUMURREJO SEMARANG CITY - Silvia Theresani Allawiyah; Thriwaty Arsal; Hamdan Tri Atmaja (Jurnal Mahasiswa Agribisnis, 2026)
This study investigates the role of social capital in empowering Women Farmer Groups (KWT) in Dusun Sumurjurang, KelurahanSumurrejo, Semarang. Using a qualitative phenomenological approach, the research examines three components of social capital: social networks, trust, and social norms, as theorized by Robert D. Putnam. Data were collected through in-depth interviews, field observations, and documentation from the KWT "Berkah Tulip Bersemi," established in 2024. Findings reveal that internal bonding networks among members are strong, supported by high interpersonal trust and gotong royong (mutual cooperation) norms. However, external bridging and linking social capital remain limited, restricting access to markets, technology, and government programs. Trust in group leaders proved critical in sustaining member participation and group cohesion. Social capital collectively contributed to collective agricultural activities, knowledge sharing, and economic empowerment, though challenges in external networking persist in this peri-urban context. This research contributes empirically to social capital theory and Social Studies education, particularly regarding rural women's empowerment in urbanizing areas. Keywords: empowerment, social capital, social network, trust, women farmer group